2023
DOI: 10.1186/s12890-023-02605-2
|View full text |Cite
|
Sign up to set email alerts
|

Days spent on non-invasive ventilation support: can it determine when to initiate VV- ECMO? Observational study in a cohort of Covid-19 patients

María P. Fuset-Cabanes,
LLuisa Hernández-Platero,
Joan Sabater-Riera
et al.

Abstract: Background The study evaluates the impact of the time between commencing non-invasive ventilation (NIV) support and initiation of venovenous extracorporeal membrane oxygenation (VV-ECMO) in a cohort of critically ill patients with coronavirus disease 2019 (COVID-19) associated acute respiratory distress syndrome (ARDS). Methods Prospective observational study design in an intensive Care Unit (ICU) of a tertiary hospital in Barcelona (Spain). All pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Indeed, NIV should be approached cautiously in cases of hypoxemic de novo ARF [37], as the primary concern is the potential for delaying necessary intubation, which can result in a worsened patient outcome [38,39]. Furthermore, it is well demonstrated that delay in intubation and NIV prolongation in COVID-19 patients may drastically affect clinical outcomes [40][41][42][43]. However, during the COVID-19 pandemic, the critical care surge capacity was exceeded by the request for mechanical ventilation for patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NIV should be approached cautiously in cases of hypoxemic de novo ARF [37], as the primary concern is the potential for delaying necessary intubation, which can result in a worsened patient outcome [38,39]. Furthermore, it is well demonstrated that delay in intubation and NIV prolongation in COVID-19 patients may drastically affect clinical outcomes [40][41][42][43]. However, during the COVID-19 pandemic, the critical care surge capacity was exceeded by the request for mechanical ventilation for patients [44].…”
Section: Discussionmentioning
confidence: 99%